Survey on Use of Quotes by Agricultural Communicators - Bob Rost; Carol Savonen; Andy Duncan (Journal of Applied Communications, 1993)
In public-information work writers may modify or generate direct quotes for news releases (non-verbatim quotes). In contrast, journalistic news writing traditionally uses verbatim quotes. How do land-grant communicators say they use quotes?